2020
DOI: 10.1038/s41598-020-59715-8
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in the elastic properties of gastrocnemius muscle heads in individuals with plantar fasciitis and its relationship with pain

Abstract: The objectives of this study were (1) to investigate the passive stiffness of the medial gastrocnemius (MG) and lateral gastrocnemius (LG) in patients with and without plantar fasciitis (PF), (2) to explore the correlation between gastrocnemius stiffness and plantar fascia thickness (PFT) as well as the intensity of pain in patients with PF, (3) to detect optimal cutoff points for stiffness of the MG and LG for identifying patients with pf. forty patients (mean age = 51.1 years ± 12.9) participated in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 31 publications
(75 reference statements)
1
25
0
2
Order By: Relevance
“…Findings from the present study revealed that approximately 40% of the PF athletes were assessed to have gastrocnemius pains during the relaxed bipedal static stance. The findings seemed to correspond to the related studies which stated that patients with PF may exhibit greater stiffness on the medial gastrocnemius when their ankles are in a relaxed position, rather than in a neutral position [ 50 ]. Supporting the studies by Tahririan et al [ 49 ], many studies went further, asserting that relieving the gastrocnemius stiffness can also simultaneously alleviate the symptoms of PF.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Findings from the present study revealed that approximately 40% of the PF athletes were assessed to have gastrocnemius pains during the relaxed bipedal static stance. The findings seemed to correspond to the related studies which stated that patients with PF may exhibit greater stiffness on the medial gastrocnemius when their ankles are in a relaxed position, rather than in a neutral position [ 50 ]. Supporting the studies by Tahririan et al [ 49 ], many studies went further, asserting that relieving the gastrocnemius stiffness can also simultaneously alleviate the symptoms of PF.…”
Section: Discussionsupporting
confidence: 87%
“…It has been widely accepted that there is a strong link between the gastrocnemius and the plantar fascia [ 50 ]. Previous studies showed that the overstretching of Achilles tendon may be attributable to a strong and long-lasting contraction of the gastrocnemius and the soleus muscles, and that this was a reasonable mechanical factor for the excessive weight-bearing of the plantar fascia [ 50 ]. Intense strain of the plantar fascia is usually accompanied by an increase in calf muscle tension [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies indicate that a tensegrity model might not be a true representation of the whole fasciomusculoskeletal system, and some evidence supports tensional propagation only to certain areas. 41…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic monitoring the mechanincal properties of fascia is contributed to understanding more information about diagnosis, monitoring disease progression and treatment response [14]. Ultrasonic shear wave elastography (USWE) is an quantitative and effective technique to evaluate the elastic properties of soft tissues, such as muscle, tendon, and fascia [15][16][17][18]19]. USWE can be used to estimate the elastic properties of a local target area through shear wave speed, insight will be gained into how the body responds to various forces and the effects of treatments.…”
Section: Introductionmentioning
confidence: 99%